The learner: Do individual differences matter? - Mihaljević-Djigunović, Jelena (Array, 2011)
The chapter focuses on affective characteristics of young foreign language learners in seven European countries. Findings of a three-year longitudinal study show that most young learners start with a very positive outlook, but differences in attitudes to FLL, motivation and language self-concept can be observed from the start. The impact of young learner characteristics is stronger by the age of 10-11 years than at the first phase of learning.